131I, 137Cs, 134Cs from Fukushima fallout at Milano, Italy - Groppi, F.; Manenti, S.; Gini, L.; Ioannidou, A. (HNPS Advances in Nuclear Physics, 2020)
Right after the Fukushima reactor accident, a systematic air and wet sampling and analysis programme was undertaken to detect and quantitatively analyze the radionuclides in the Fukushima fallout in Milano, Italy. Radionuclides from Fukushima were first detected at Milano region in a rain water sample, collected during March 27-28, 2011 with the concentrations of 131I and 137Cs isotopes in the rainwater to be equal with 0.89 Bq/L and 0.12 Bq/L, respectively. The concentration of 131I in goat and cow milk samples from a farm in Monte Rosa mountain, were 0.25 and 0.21 Bq/L, respectively. Increased atmospheric radioactivity was detected on air filter taken on 30 March 2011, while the maximum activity of 467 μBq/m3 occurred at April 3-4, 2011. A week later the activities had fallen to about 50% of peak values, with a general increasing trend over the following days. In the time period of one month after the nuclear accident, concentrations of 137Cs and 134Cs in air as high as 63 μBq/m3 and 61 μBq/m3, respectively were recorded. The presence of more than one peaks of 131I and 137,134Cs till April 11, 2011, indicates that 131I and 137,134Cs were continuously transferred from Fukushima, Japan to Italy. According to the measurements, airborne activity levels remain of no concern for public health in Italy.